Scaffolding self-regulated learning through student-generated quizzes. (July 2019) - Jones, Jennifer A
Self-regulated learning assumes learners are active agents who can establish and make progress toward learning goals. Classroom activities can facilitate the emergence of self-regulated learning. One strategy to encourage self-regulated learning is to ask students to develop questions for a quiz or examination. The process of developing questions scaffolds higher-order thinking. Rather than just memorize or apply the material, students must think about how to evaluate their knowledge of the material. The purpose of this study was to identify students' perceptions about the experience of developing questions for a quiz or examination. Three separate and slightly different quiz-building activities were conducted in a large undergraduate classroom. A follow-up student perception survey indicates that students (a) found this activity valuable for learning, (b) were concerned about the quality of questions produced, and (c) preferred team-based activities over individual activities. This article suggests ways to improve this activity and offers suggestions for future research.